1990
DOI: 10.1080/11250009009355704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short postcapture confinement on plasma reproductive hormone and corticosterone profiles inRana esculentaduring the sexual cycle

Abstract: The effects of short-term confinement (24 hours) on the plasma levels of gonadal hormones and corticosterone have been evaluated in Rana esculenta, which is widely used in amphibian reproductive physiology studies. A 24-h confinement has been chosen since this is the time that usually elapses from frog capture to utilization. Although short confinement does not influence the morphological aspect of gonads, genital tracts (oviduct in the female) and secondary sexual characters (thumbpads in the male), it causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0
4

Year Published

1992
1992
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 27 publications
7
24
0
4
Order By: Relevance
“…On the contrary, in Rana esculenta testosterone affected EBP binding capacity. Since our previous studies show that in Rana esculenta circulating sex steroid changes paralleled EBP fluctuations throughout the reproductive cycle, with the highest levels of EBP coinciding with the resumption of reproductive activity (Paolucci and Di Fiore, 1994), it is plausible that both 17β-estradiol and testosterone sustain EBP concentration in the female of this species, characterized by, as with other lower vertebrates, very high levels of circulating androgens (Delrio et al, 1979;Paolucci et al, 1990;Stuab and De Beer, 1997). Whether or not androgens act as estrogens, after their aromatization to 17β-estradiol we do not know at present.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…On the contrary, in Rana esculenta testosterone affected EBP binding capacity. Since our previous studies show that in Rana esculenta circulating sex steroid changes paralleled EBP fluctuations throughout the reproductive cycle, with the highest levels of EBP coinciding with the resumption of reproductive activity (Paolucci and Di Fiore, 1994), it is plausible that both 17β-estradiol and testosterone sustain EBP concentration in the female of this species, characterized by, as with other lower vertebrates, very high levels of circulating androgens (Delrio et al, 1979;Paolucci et al, 1990;Stuab and De Beer, 1997). Whether or not androgens act as estrogens, after their aromatization to 17β-estradiol we do not know at present.…”
Section: Discussionmentioning
confidence: 77%
“…Although our previous observations (Paolucci and Di Fiore, 1994) indicate that TBP binding capacity fluctuations in the female of Rana esculenta did not show any relationship with the reproductive cycle, we decided to monitor the possible changes in TBP binding capacity following the sex steroid treatment, since androgen plasma levels are, in the female of Rana esculenta, higher than in the male (Paolucci et al, 1990). Up to now a role for such high levels of circulating androgens in the females has not been demonstrated with certainty (Del Rio et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Although potential effects on plasma hormone levels following capture and short-term confinement have not been investigated, we are confident that the changes in plasma hormone levels detected in this study have given a reliable plasma hormone profile of R. dalmatina throughout the sexual cycle. In fact, in Rana esculenta the annual pattern of plasma androgens, as well as their correlation with the secondary sexual character cycle, is not significantly different in just captured and short-term captive frogs (Paolucci et al, 1990). In R. dalmatina, T peaks during the breeding season.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, the lowest release of PGF2a and oestradiol from ovarian tissues was found in June, despite the fact that concentrations of plasma PGF2a and oestradiol are high during this month. In previous studies it was suggested that the major source of these two hormones, during June, may be the interrenal gland (Pavgi and Licht, 1989;Fasano et al, 1991 (Mori et al, 1989 (Salthe and Mecham, 1974 (Paolucci et al, 1991;, in Rana catesbeiana (Licht et al, 1983), in rough skinned newt, aricha granulosa (Moore efe Zoeller, 1985), and in crested newt, Triturus carnifex (Gobbetti et al, 1991b, c . In addition, in Triturus carnifex, treatment with PGE2 decreased androgen secretion, which was modified by captivity (Gobbetti and Zerani, 1992b), whereas a progesterone secretion which was not modified by captivity was increased after treatment with PGE2 This work was supported by a grant to A. Gobbetti from M.U.R.S.T.…”
Section: Experiments In Vitromentioning
confidence: 99%